Restructuring Wealth Ownership - J., Basil (USM, 1975)
The New Economic Policy ( NEP ) is framed in terms of achieving the twin objectives of eradicating poverty, by raising income levels and increasing employment opportunities, and of restructuring Malaysian Society, so as to reduce and eventually eliminate the identification of race with economic function.